2006
DOI: 10.1103/physreve.73.046604
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous curvature cancellation in forced thin sheets

Abstract: In this paper we report numerically observed spontaneous vanishing of mean curvature on a developable cone made by pushing a thin elastic sheet into a circular container [1]. We show that this feature is independent of thickness of the sheet, the supporting radius and the amount of deflection. Several variants of developable cone are studied to examine the necessary conditions that lead to the vanishing of mean curvature. It is found that the presence of appropriate amount of radial stress is necessary. The de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…1 (Q 2 ) is an observable which has been measured at JLab/Hall C (124). One can then use the measured value on the lhs of the sum rule of Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 (Q 2 ) is an observable which has been measured at JLab/Hall C (124). One can then use the measured value on the lhs of the sum rule of Eq.…”
mentioning
confidence: 99%
“…At the real photon point, both observables yield the Baldin sum rule value for α E1 + β M 1 (30). The data point at Q 2 = 0.3 GeV 2 (left panel) is from JLab/HallC (124). In order to completely fix the term of O(Q 4 ) in the subtraction function T N B 1 (0, Q 2 ), one needs to determine the low-energy coefficient b3,0.…”
mentioning
confidence: 99%
“…In this reference, one can find ansatz-based discussions and numerical simulations of the regular cone. For more recent numerical simulations, see Liang and Witten (2006). In , minimizers of the free elastic energy have been described in some detail under the assumption of small deflections and rotational symmetry.…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…As the thickness of the elastic sheet goes to zero, they found that within the numerical accuracy, the radial curvature C rr and the azimuthal curvature C θθ are equal and opposite at the rim, so that the mean curvature virtually vanishes there. Though it arises from mechanical equilibrium, the phenomenon is purely geometric: it does not involve material parameters [1,5]. The von Kármán equations must be able to account for the cancellation effect, but this has not been done yet.…”
Section: Introductionmentioning
confidence: 99%
“…It is nonlocal because it depends on the overall geometry of the sheet. The curvature does not vanish when one modifies this geometry by cutting the sheet radially or by replacing the flat sheet by a cone [5]. The effect also depends on the nonlocal forcing at the vertex.…”
Section: Introductionmentioning
confidence: 99%